Regional Economic Outlook, October 2012, Sub-Saharan Africa : Maintaining Growth in an Uncertain World. (Regional Economic Outlook, 2012)
Economic conditions in sub-Saharan Africa have remained generally robust despite a sluggish global economy. The near-term outlook for the region remains broadly positive, and growth is projected at 5u percent a year in 2012-13. Most low-income countries are projected to continue to grow strongly, supported by domestic demand, including from investment. The outlook is less favorable for many of the middle-income countries, especially South Africa, that are more closely linked to European markets and thus experience a more noticeable drag from the external environment. The main risks to the outlook are an intensification of financial stresses in the euro zone and a sharp fiscal adjustment in the US--the so-called fiscal cliff.